2021
DOI: 10.3390/su13115864
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Research on the Use of R1234yf as an Environmentally Friendly Fluid in the Organic Rankine Cycle

Abstract: ORC technology is one of the most promising technologies for the use of residual energy in the generation of electrical energy, offering simple and environmentally friendly alternatives. In this field, the selection of working fluids plays an important role in the operation of the cycle, whether in terms of the energy efficiency or the minimization of environmental impacts. Therefore, in this paper, a comprehensive review is presented on the use of R1234yf refrigerant and its mixtures as working fluids in ORC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Presently, the use of refrigerants such as hydrocarbons (HCs), hydro-fluoro-olefin (HFO), R744 (carbon dioxide), and environmentally safe nanorefrigerants can reduce both ozone depletion potential and global warming potential [15]. It has been found that replacing R-134a with R1234yf [16] had similar thermal performance and with better environmental benefits. The typical compressor is driven by electrical power and the specific power consumption varies from 0.33 kW/kW of cooling at a condenser temperature of 26 • C to 0.4 kW/kW of cooling at 40 • C condenser temperature [17].…”
Section: Vapor Compression Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, the use of refrigerants such as hydrocarbons (HCs), hydro-fluoro-olefin (HFO), R744 (carbon dioxide), and environmentally safe nanorefrigerants can reduce both ozone depletion potential and global warming potential [15]. It has been found that replacing R-134a with R1234yf [16] had similar thermal performance and with better environmental benefits. The typical compressor is driven by electrical power and the specific power consumption varies from 0.33 kW/kW of cooling at a condenser temperature of 26 • C to 0.4 kW/kW of cooling at 40 • C condenser temperature [17].…”
Section: Vapor Compression Methodsmentioning
confidence: 99%
“…V ij = W j × R ij (16) The outcome of above Equation ( 16) results in the set of best and worst solutions, and are obtained using Equations ( 17) and (18), respectively.…”
Section: Determine Best and Worst Cooling Strategy For A Given Criterionmentioning
confidence: 99%
“…• R1233zd(E), which serves as a working fluid in laboratory configurations for a CB [19,20]. • R1234yf, which is under discussion as a potential substitute for R134a [21]. • R290 (Propane), which finds application in refrigeration or HP systems [22].…”
Section: Discharging Processmentioning
confidence: 99%
“…However, the working fluid R1234yf has never been used so far in ORC processes. TRL3 is achieved because the technology concept has been investigated, formulated and verified by numerical simulation 58 . TRL4 is not achieved because there is no prototype or experimental investigations yet.…”
Section: Technology Readiness Levelmentioning
confidence: 99%